MONITORING AKSES LOKER DOSEN MENGGUNAKAN EMBEDDED SYSTEM DENGAN ANTARMUKA ANDROID - Riki Ruli A Siregar; Jaka Mahardika (Sekolah Tinggi Teknik - PLN, 2015)
At a college lecturer supplied lockers are often used for collecting student assignments.However, the faculty locker was not locked so that everyone can open lockers at any time because itis the students often do not collect duties in accordance with the specified time, and there is even amissing student assignments.The method used to solve the problem by using the prototype method, steps done is to identifythe problems that exist in the lockers, analyze the system and tools used, data collection, systemdesign and manufacturing tools and programs. In the android-based monitoring access lockers withembedded wireless system can choose who can access the lockers, the android-based devices areused as an interface for access to open the locker using the username and password at login time.Since the number of Android users and can also be used in a mobile while accessing the lockerandroid chosen as support for accessing the lockers.The results obtained so that lecturers lockers can be opened at any time and can find out whoopened the locker lecturer on history report contained in the application server admin locker accessmethod using embedded systems with android interface can be implemented on the problemslocker lecturer